Resource potential of bioethanol and biodiesel production in Ukraine - Kaletnik Grygorii; Prutska Olena; Pryshliak Natalia (Visegrad Journal on Bioeconomy and Sustainable Development, 2014)
Recently the biofuel production has significantly increased all over the world. In Ukraine this trend is increasing under the influence of such factors as the need to overcome the energy shortage, reduce dependence on oil imports and availability of powerful natural resource potential. The aim of the article is assessment of the resource potential of bioethanol and biodiesel production in Ukraine both for domestic needs and for export. Data from the State Statistics Committee of Ukraine on production and exports volumes of major bioenergy crops is analyzed and the potential volume of biofuels production in Ukraine is calculated for achievement the research objectives. The importance of shift from exportoriented agriculture to energy crops production for their processing into biofuels within the country is described